USM RECREATION PARK (TRU) - A SUSTAINABLE ASSET OF THE UNIVERSITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 11 January 2017 – The University Recreation Park (Taman Rekreasi Universiti TRU) is an important asset of Universiti Sains Malaysia (USM) in further elevating its reputation as a university that champions sustainability issues.